A motivação de mulheres para prática do treinamento funcional, no município de Barcarena-PA - FACUNERY, Emanuele de Medeiros (2023)
The regular practice of physical exercises is closely related to health promotion and positive lifestyle, considering the visibility that Functional Training (FT) has acquired over the past decades, this study aims to investigate the motivations of women to practice FT in the city of Barcarena-PA, seeking to identify the determinants for the adherence to this activity. To thiend, a field research was carried out, with data collected through the application of a questionnaire with open and closed questions. The subjects of the research were 30 (thirty) women who practice functional training, with ages ranging from 23 to 52 years (35.83 ± 6.83 years). The analysis of the interviews allowed us to identify the most relevant aspects that lead women to participate in physical activity, being aesthetic (33.3%), mental health (26.7%), treatment or prevention of diseases (10%), sedentarism and a more active life (43.3%) the highlighted categories. The reason directed to the practice of physical exercise is an important factor for personal determination to start or remain in the activity, on the other hand, motivation can also be developed in the very act of training through intrinsic motivation.